Development and Validation of a High-Performance Liquid Chromatographic Method for the Determination of Cinitapride in Human Plasma - Boovizhikannan Thangabalan; Getu Kahsay; Tadele Eticha (Journal of Analytical Methods in Chemistry)
A precise and reliable reversed-phase high-performance liquid chromatographic method with ultraviolet detection was developed and validated to determine cinitapride in human plasma. After liquid-liquid extraction, chromatographic separation was achieved on a Nucleosil C18 (25 cm × 4.6 mm, 5 µm) column with an isocratic elution consisting of 10 mM ammonium acetate (pH 5.2), methanol, and acetonitrile, 40 : 50 : 10, v/v/v. The developed method was validated as per US FDA guidelines for its linearity, selectivity, sensitivity, precision, accuracy, and stability. Satisfactory findings were obtained from the validation studies. The linearity range of the method was 1 to 35 ng/mL while the extraction recovery of cinitapride in human plasma was more than 86%. The percent coefficient of variation of both intraday and interday precision was ≤7.1%.